Geometry of Invariant Tori of Certain Integrable Systems with Symmetry and an Application to a Nonholonomic System - Fassò, F.; Giacobbe, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
Bifibrations, in symplectic geometry called also dual pairs, play a relevant role in the theory of superintegrable Hamiltonian systems. We prove the existence of an analogous bifibrated geometry in dynamical systems with a symmetry group such that the reduced dynamics is periodic. The integrability of such systems has been proven by M. Field and J. Hermans with a reconstruction technique. We apply the result to the nonholonomic system of a ball rolling on a surface of revolution.